Human resource management practices of multinational companies in Malaysia - Noreha Halid; Rozhan Othman (Penerbit Universiti Kebangsaan Malaysia, 1998)
With the globalization of business, corporations have to deal with a more complex environment. One area that has received considerable attention in international management is human resource management (HRM). Some researchers argue that the HRM practices of multinational companies (MNCS) are likely to reflect the local conditions rather than be shaped by the corporation's country of origin. This suggests that the HRM practice of MNCs should not be too different from local firms. However, there is evidence that MNCs in Malaysia exhibit distinct differences from Malaysian firms in their HRM practice. This study compares the HRM practices of Malaysian firms and MNCs. The findings suggest that contingencies other than firm nationalily are stronger predictors of HRM practice. We argue that the proposed relationship between ;MNCs and HRM practice is a bit simplistic and ignores the complex interaction of variables shaping HRM practice in MKCs.